PEMANFAATAN SISTEM MASSIVE OPEN ONLINE COURSE (MOOC) TERHADAP PENINGKATAN KINERJA ANALIS KEBIJAKAN - Handyka Oktra Rajagukguk; Nurhattati Nurhattati; Kamaludin Kamaludin (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the impact and influence of Massive Open Online Courses (MOOCs) on improving the skills of Functional Policy Analysts (JFAK) in the government sector. The research method used is a literature study, which collects and analyzes various relevant sources regarding the influence of MOOCs on competency development in the public sector. The results of the study indicate that MOOCs have a significant positive impact on improving the technical and managerial skills of JFAK, with a focus on developing capabilities in policy analysis, program management, and data-driven decision-making. MOOC-based training programs enable increased accessibility, flexibility, and cost efficiency for JFAK, as well as facilitate their ability to keep up with the latest developments in public policy. Based on these findings, this study recommends increased government support for the integration of MOOCs into training for Policy Analyst Functional Positions to accelerate the competency improvement process, as well as the need for digital literacy training to maximize the utilization of this platform among JFAK.